Adsorption of Zerovalent Iron Nanoparticles in the Inorganic Fraction of Volcanic Soils - Escudey-Castro, A; Escudey-Castro, A; Gacitua-Santalices, M; Gacitua-Santalices, M (Springer Science and Business Media Deutschland GmbH, 2022)
Zerovalent (ZVI) iron has been used in environmental remediation, but the environmental fate of its nanoparticles (NZVI) is hard to find. The present study aimed to characterise the adsorption processes of commercial ZVI in the inorganic fraction of volcanic soils, contributing to the knowledge of the adsorption process on the whole soil. Volcanic soil samples were obtained by calcination method and characterised. A nano-ZVI stable suspension is prepared and characterised to know its size-particle distribution. Adsorption points (kinetical and isothermal) were obtained by adapting the procedure for homogeneous analyte adsorption. Kinetical, solute transport and isothermal adsorption and desorption models were adjusted to obtain more conclusive information about the process. Analysis of the results revealed that adsorption is a fast process. The inorganic fraction of an Andisol presented pH-dependant surface charge, requiring highly consistent control of the working pH to obtain proper adsorption points. Isothermal adsorption indicates that a combination of physical and chemical mechanisms contributes to the NZVI adsorption process. Desorption studies suggested chemisorption on specific surface-active sites of adsorbents, with the inorganic fraction of soil irreversibly retaining most of the NZVI particles. NZVI become irreversibly adsorbed over the inorganic fraction of soils, extending particle reactivity through time, affecting the stability of organic matter and microbial communities. In turn, this increases the possibility for plant uptake. Nevertheless, there is a low risk for the transport of NZVI through soil profiles or co-transport of other components that becomes adsorbed over iron, lowering the risk of aquifer pollution. © 2022, The Author(s).